Acute and long-term pathological effects of COVID-19 on the placenta during second trimester and labor - Fatih Taş; Fikri Erdemci̇; Mehmet Yilmaz; Fırat Aşir; Osman Özüdoğru; Engin Deveci̇ (Revista de Investigaciones Universidad del Quindío, 2023)
Background: COVID-19 pandemic has affected all the world. The consequence of the COVID-19 infection causes many disorders in many organs, one of them is the placenta. COVID-19 disease has long-term effects on various tissues after recovery. The aim of this study was to investigate the placentas of pregnant women with healthy, COVID-19 positive during the second trimester and labor.